A systematic approach to learning robot programming with ROS - Newman, Wyatt S. (CRC Press, Taylor & Francis Group, 2018)
The book explores the organization of ROS, how to understand ROS packages, how to use ROS tools, how to incorporate existing ROS packages into new applications, and how to develop new packages for robotics and automation. It also facilitates continuing education by preparing the reader to better understand the existing on-line documentation.